Diagnóstico del sistema de gestión de mantenimiento para la producción de energía eléctrica del bloque 21 de la empresa Petroamazonas Ep. - Naranjo Silva, Héctor Sebastián (2016)
The oil sector was an important item that solved the country's economy for 40 years, Ecuador is in daily oil development by creating stations and daily work to the people, when the operator Petroamazonas EP. it is in a phase of certifications and personnel adjustment to new policies of production and exploitation, hence the emergence of this research. The research was based on the programming of industrial production based on the need to improve the inefficient management system in the area of electricity generation 21 Block of the maintenance department. Its methodology of inquiry was based on the scientific method of research and exploratory character, with analysis of historical data that generate a quantitative approach throughout the investigation; the solution of the problem had two main points, first redesign management system control the power plant, with the creation of software daily monitoring of activities with data and graphics productivity, as the second item further generating an index, compilation and creation of manual procedures.